The Lesbianism of Celie in the Novel “The Color Purple” by Alice Walker (Psychological Approach) - Ramli Ramli; Muhammad Hairul Rizal (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2021)
The aims of the research are to analyse the aspects dan the factors that influence Celie, the main character being a lesbian in the novel “The Colour Purple” by Alice Walker. The research applied descriptive method by using psychological approach through the principle of Adler’s personality theory. The data source was taken from all the words, dialogues, phrases, and, sentences in Alice Walker's novel "The Colour Purple". The result showed that the novel “The Colour Purple” written by Alice Walker portrayed Celie being a lesbian because of some aspects and factors which  influenced her point of view about relationships and sexual orientation. Her personality changed her life through the aspects such as inferiority, superior, creative self, self-conscious and pseudo purpose that related to her gender and lesbian. Other factors also influenced her character and personality of loving with same gender because of her lifestyle personality and social interests.